The influence of singly charged ions on the translational motion of molecules in extremely dilute amide solutions - Bulavin, Viktor Ivanovych; Vunik, Ivan Nikolajevych; Kramarenko, Andrii Viktorovych; Rusinov, Alexandr Ivanovych (Національний технічний університет "Харківський політехнічний інститут", 2021)
The type of short range solvation of Li⁺ , Na⁺ K⁺ , Rb⁺ , Cs⁺ , NH₄⁺ , Cl⁻ , Br⁻ , I⁻, ClO₄⁻ ions has been determined and analyzed in formamide (FA), Nmethylformamide (MFA), N-dimethylformamide (DMF) at 298.15 K. In order to determine the type of ion solvation we used familiar-variable quantitative parameter (d – ri), where d is the translational displacement length of ion, ri is its structural radius. It was found that the difference (d – ri) is equal to the coefficient of attraction friction (CAF) of ions normalized to the solvent viscosity and hydrodynamic coefficient. The sign of the CAF is determined by the sign of the algebraic sum of its ion-molecular and intermolecular components. In amide solutions the studied cations are cosmotropes (positively solvated ((d – ri) > 0), structure-making ions) and anions are chaotropes (negatively solvated ((d – ri) < 0 ), structurebreaking ions). In the amide series, regardless of the sign (d – ri), the near-solvation enhances, which can be explained by the weakening of the specific interaction between the solvent molecules. The decrease of d and respectively (d – ri) with increasing cation radius in a given solvent is the result of weakening of its coordinating force due to the decrease of charge density in the series Li⁺–Na⁺–K⁺–Rb⁺–Cs⁺ . The increase of d (and (d – ri), correspondingly) for the ions studied in the series FA-MFA-DMF can be explained by the weakening of intermolecular interactions in this series, which leads to the strengthening of solvation. It was found that for the halide ions in the series FA-MFA-DMF the regular growth of d parameter is explained by the weakening of the solvent structure. It was shown that Li⁺ ion with the lowest diffusion coefficient among cations and the highest d value forms kinetically stable complexes in amide solutions.

Встановлено та проаналізовано тип ближньої сольватації іонів Li⁺ , Na⁺ K⁺ , Rb⁺ , Cs⁺ , NH₄⁺ , Cl⁻ , Br⁻ , I⁻, ClO₄⁻ в формаміді (ФА), Nметілформаміде (МФА), N,N -діметілформаміде (ДМФА) при 298,15 К. Для визначення типу сольватації іонів використаний обгрунтований нами знакозмінний кількісний параметр (d – ri), де d - довжина трансляційного зміщення іона, ri - його структурний радіус. Встановлено, що різниця (d – ri) дорівнює коефіцієнту атракціонного тертя (КАТ) іонів, нормованому на в’язкість розчинника і гідродинамічний коефіцієнт. Знак КАТ визначається знаком алгебраїчної сумі його іон-молекулярної і міжмолекулярної складових. У амідних розчинах вивчені катіони-космотропи (сольватовані позитивно ((d – ri)> 0), іони-структуроутворювачі), а аніони-хаотропи (негативно сольватовані ((d – ri). В ряду амідів незалежно від знака (d – ri) посилюється ближня сольватація, що пояснюється послабленням специфічної взаємодії між молекулами розчинника. Зменшення d і відповідно (d – ri) зі зростанням радіуса катіона в окремо взятому розчиннику є результатом послаблення його координуючої сили внаслідок зменшення густини заряду в ряду Li⁺–Na⁺–K⁺–Rb⁺–Cs⁺. Збільшення d (відповідно і (d – ri)) для досліджених іонів в ряді амідів ФА–МФА–ДМФА можна пояснити послабленням в цьому ряді міжмолекулярних взаємодій, що зумовлює посилення сольватації. Установлене для галогенід-іонів в ряді ФА–МФА–ДМФА закономірне зростання параметра d пояснюється зменшенням структурованості розчинника. Показано, що іон Li⁺ з найменшим коефіцієнтом дифузії і найбільшим значенням d утворює кінетично стабільні комплекси в амідних розчинах.
Закономірності впливу однозарядних іонів на поступальну рухомість молекул в гранично розбавлених амідних розчинах
Keywords: monatomic ions; diffusion; positive and negative solvation; diffusion displacement length; одноатомні іони; довжина дифузійного зміщення